Orthodontic Fixed Retainer and Unwanted Movements of Lower Anterior Teeth: A Case Report - Maria Francesca Sfondrini; Maurizio Pascadopoli; Sergio Beccari; Giovanna Beccari; Cinzia Rizzi; Paola Gandini; Andrea Scribante (Hindawi Limited, 2022)
The use of fixed retainers at the end of an orthodontic treatment has become a standard practice. Nonetheless, orthodontic relapse can still occur, requiring retreatment in the most severe cases. This case report describes a patient with a mandibular canine to canine fixed retainer presenting uncontrolled torque on all lower anterior teeth, probably due to tongue thrust and/or activation of the wire. Multibracket orthodontic treatment was performed, and an orthodontic lingual sectional was used to control (reposition) the root movement of the lower right cuspid. This case highlights the need for clinicians and patients to be aware of the potential problems associated with bonded retainers. In addition, patients with an orthodontic fixed retainer need regular short-term observation by an orthodontist in order to detect any adverse movements and long-term control by a general dentist.